Effects of Social Support, Functional Status, and Depression on the Quality of Life of Stroke Patients: A Meta-Analysis - Anwar Wahyudi; Didik Gunawan Tamtomo; RB Soemanto (Journal of Health Promotion and Behavior, 2020)
Background: Stroke patients have physical, social, and psychological disorders. It inhibits their daily activities, thus affecting the quality of life. This study aimed to analyze the effect of social support, functional status, and depression on the quality of life of stroke patients.Subjects and Method: This study was a meta-analysis study. The data were obtained from Clinical Key, DOAJ, PubMed, Science Direct, Proquest, Scopus, and Google Scholar. The keywords were "social support" AND "functional status" AND "depression" AND "quality of life "AND" stroke". The articles were published from January 1991 to September 2020. The articles studied were full-text-articles with a cross-sectional and cohort study design. The articles were collected using the PRISMA diagram and analyzed using the RevMan 5.3 program.Results: This study obtained 12 articles consisted of 2,015 selected stroke patients. The result of the meta-analysis showed that social support had a significant positive effect on the quality of life of stroke patients (b= 0.03; 95% CI= 0.02 to 0.05; p= 0.0001), functional status had a significant positive effect on the quality of life of stroke patients (b= 0.63; 95% CI= 0.52 to 1.08; p=0.0001), and depression had a significant negative effect on the quality of life of stroke patients (b= -0.18; 95%CI= -0.26 to -0.10; p=0.0001).Conclusion: Social support and functional status improve the quality of life of stroke patients. Depression reduces the quality of life of stroke patients.Keywords: social support, functional status, depression, quality of life, strokeCorrespondence: Anwar Wahyudi. Masters Program in Public Health, Universitas Sebelas Maret, JL. Ir Sutami 36A, Surakarta 57126, Central Java. Email: arwanwahyudi851@gmail.com. Mobile: +62813106121049.Journal of Health Promotion and Behavior (2020), 05(04): 284-295https://doi.org/10.26911/thejhpb.2020.05.04.06.